Mechanisms of in vitro development of resistance to metronidazole in Trichomonas vaginalis - Rasoloson, Dominique; Vanacova, Stepanka; Tomkova, Eva; Razga, Jakub; Hrdy, Ivan; Tachezy, Jan; Kulda, Jaroslav (Microbiology (Reading, England), 2002)
Development of resistance against metronidazole and mechanisms responsible for this process were studied in a sexually transmitted pathogen of humans, Trichomonas vaginalis. Monitoring of changes in metabolism and protein expression that accompanied increasing resistance of strains derived from a common drug-susceptible parent (TV 10-02) showed the multistep character of the process. The aerobic type of resistance known to occur in isolates from patients non-responsive to treatment appeared at the earliest stage, followed by development of the anaerobic type of resistance which was accompanied by gradual loss of hydrogenosomal proteins associated with drug-activating pathways [pyruvate:ferredoxin oxidoreductase (PFOR), hydrogenase, ferredoxin]. Unexpectedly, the loss of PFOR did not result in acquisition of full anaerobic resistance, thus indicating an alternative source of electrons required for the drug activation. These data suggest involvement of the oxidative decarboxylation of malate in hydrogenosomes, catalysed by NAD(+)-dependent malic enzyme and subsequent transfer of reduced equivalents to the drug via NADH:ferredoxin oxidoreductase and ferredoxin. Accordingly, all components of this pathway were eliminated before the resistance was fully developed. Resistant Trichomonas vaginalis compensated the impaired function of hydrogenosomes by enhanced conversion of pyruvate to lactate in the cytosol. Further analysis of the two key enzymes involved in metronidazole activation by Northern blotting and assay for nascent mRNA showed that the insufficient expression of the PFOR protein results from decreased gene transcription, while down-regulation of malic enzyme is controlled at the mRNA level.
Keywords: Drug Resistance; Transcription, Genetic; Pyruvate Synthase; techniky in vitro; Blotting, Northern; Metronidazole; ketonoxidoreduktasy; léková rezistence; Antitrichomonal Agents; Trichomonas vaginalis; genetická transkripce; northern blotting; Animals; lidé; metronidazol; Humans; zvířata; In Vitro Techniques; antitrichomonádové látky; pyruvátsynthasa; Ketone Oxidoreductases